Aplikasi Sirkulasi Kualitatif pada Interior Pasar Atom Mall di Surabaya - Jennifer Jonson (Intra, 2017)
Pasar Atom Mall is shopping center that offers variety of fashion, gold and jewelry, food and beverages, up to bank. This mall is continuation of the Pasar Atom which connected via circulation. Furthermore, Circulation is the element that organizes and links between part of different shopping mall, such as shops, anchor stores, and other mall facilities. According to Peter Coleman, the organization of the circulation can be separately identified into functional and qualitative requirements. This research use qualitative requirements as a benchmark. Qualitative circulation requirements are recommended planning based on consideration of the use of a strip mall visitor’s perspective and can give character to shopping center to make the facility more memorable and enjoyable. The purpose of this research was to determine the circulation application in the Pasar Atom Mall interior with qualitative circulation requirements. The result is Pasar Atom Mall has applied the requirements of qualitative circulation in appropriate with the parameters, even though there are still some requirements are not applied. Circulation qualitative which are applied including the identity of the circulation area recognized by visitors, arrangement of space based on the importance and function space, environmental comfort, provide chilled environment in summer, mall environmental care, and provide positive experience to visitors by providing seating facilities, informal meeting rooms, and the quality of the interior elements in the mall.